Technical Note: MR‐visualization of interventional devices using transient field alterations and balanced steady‐state free precession imaging. Issue 11 (20th October 2015) - Eibofner, Frank; Martirosian, Petros; Würslin, Christian; Graf, Hansjörg; Syha, Roland; Clasen, Stephan
Abstract : Purpose: In interventional magnetic resonance imaging, instruments can be equipped with conducting wires for visualization by current application. The potential of sequence triggered application of transient direct currents in balanced steady‐state free precession (bSSFP) imaging is demonstrated. Methods: A conductor and a modified catheter were examined in water phantoms and in an ex vivo porcine liver. The current was switched by a trigger pulse in the bSSFP sequence in an interval between radiofrequency pulse and signal acquisition. Magnitude and phase images were recorded. Regions with transient field alterations were evaluated by a postprocessing algorithm. A phase mask was computed and overlaid with the magnitude image. Results: Transient field alterations caused continuous phase shifts, which were separated by the postprocessing algorithm from phase jumps due to persistent field alterations. The overlaid images revealed the position of the conductor. The modified catheter generated visible phase offset in all orientations toward the static magnetic field and could be unambiguously localized in the ex vivo porcine liver. Conclusions: The application of a sequence triggered, direct current in combination with phase imaging allows conspicuous localization of interventional devices with a bSSFP sequence.